Analisis Opini Publik Gerakan Penolakan Rancangan Undang-Undang Kitab Hukum Pidana Oleh Badan Eksekutif Mahasiswa (BEM) UNMUL - Apriani, Gita; Hairunnisa; Nurliah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The purpose of this study was to find out how the Public Opinion Movement Rejected the Draft Criminal Code by the Student Executive Board (BEM) UNMUL.The focus of the research consists of the elements of forming public opinion, namely: controversial issues or issues being contested, the public who are spontaneously enticed toinvolve themselves in problems and interactions, discussions, exchange of ideas and debates on disputed issues from individuals in the public then produce an opinion collective and expressive. Key informants namely; UNMUL BEM students, BEM Head informants, Action Coordinators, and Action Public Relations, as well as other informants, namely Mulawarman University students. Data collection techniques were carried out by means of interviews and documentation. The data analysis technique used is the interactive model data analysis proposed by Miles and Huberman. The results of this study show that there is a controversial issue that is being contested through media distribution which has attracted the attention of the opinion leader, namely BEM KM UNMUL. With conceptual ideas, they exert influence as a student organization at Mulawarman University, one of which is by using social media Instagram, through a collection of people who are interested in controversial issues, namely student members of BEM who hold consolidations, discussions, to achieve goals with propaganda #MosiTidakPercaya #ReformasiDikorupsi. The public opinion of the rejection movement resulted in a pro attitude by Mulawarman University students knowing and following controversial issues through media information used by BEM. Keywords: BEM KM UNMUL, RUUKUHP, Public Opinion